2011
DOI: 10.1007/s00210-011-0668-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the hydroalcoholic extract of Phyllanthus niruri and its isolated compounds on cyclophosphamide-induced hemorrhagic cystitis in mouse

Abstract: The effects of Phyllanthus niruri hydroalcoholic extract and the isolated compounds quercetin, rutin, and gallic acid were examined in the mouse model of cyclophosphamide (CYP)-induced hemorrhagic cystitis (HC). HC was induced by a single CYP injection (300 mg/kg, IP), and the animals were evaluated 4 and 6 h after. Some animals were orally treated with the reference compound 2-mercaptoethane sodium sulfonate (Mesna) 80 mg/kg (30 min before CYP) and 160 mg/kg (2 h after CYP). Other groups were treated with P. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 48 publications
2
25
0
Order By: Relevance
“…For instance, rutin decreased paw edema induced by carrageenan and arthritis induced by adjuvant plus carrageenan in rats (Guardia et al, 2001;Rotelli et al, 2003). It also reduced nociception induced by glutamate in mice paws (Lapa et al, 2009), renal inflammation induced by cysplatin in rats (Arjumand et al, 2011) and cystitis induced by cyclophosphamide in mice (Boeira et al, 2011). These studies reinforce the possibility of rutin's role in the effects observed in CBDO-induced pancreatitis in rats.…”
Section: Discussionsupporting
confidence: 61%
“…For instance, rutin decreased paw edema induced by carrageenan and arthritis induced by adjuvant plus carrageenan in rats (Guardia et al, 2001;Rotelli et al, 2003). It also reduced nociception induced by glutamate in mice paws (Lapa et al, 2009), renal inflammation induced by cysplatin in rats (Arjumand et al, 2011) and cystitis induced by cyclophosphamide in mice (Boeira et al, 2011). These studies reinforce the possibility of rutin's role in the effects observed in CBDO-induced pancreatitis in rats.…”
Section: Discussionsupporting
confidence: 61%
“…The levels of MDA were measured as indicative of oxidative stress, according to the method described by Boeira et al . (). The bladders of five mice per group were collected 6 h after CPA injection.…”
Section: Methodsmentioning
confidence: 97%
“…Flavan-3-ols are the basic constitution of condensed tannins. Flavonols such as quercetin, quercitrin, and rutin demonstrated anti-inflammatory and antioxidant activities [ 151 , 171 , 178 , 195 , 203 , 224 ].…”
Section: Chemical Constituentsmentioning
confidence: 99%